PERAN AGILITY TERHADAP PERFORMA PERTANDINGAN DALAM OLAHRAGA PERMAINAN SQUASH - Palgunadhi, Finaldhi; Nuryanti, Widy Dewi; Kurniawan, Tian; Hidayat, Iwa Ikhwan; Haryono, Tono; Imanudin, Iman; Rusdiana, Agus (Fakultas Ilmu Keolahragaan Unimed, 2025)
This study aims to investigate whether there is a relationship between agility and match ranking among athletes in the sport of squash. The research approach used is a correlational study. The sample consisted of 18 national squash athletes from Bandung City (9 males and 9 females). The instruments used in this study were the agility T-test to measure athletes' agility ability, and internal matches using a round-robin system (best of 5 games) to determine athlete rankings. The analysis results showed no significant relationship between agility and overall match ranking in squash athletes. However, when analyzed by gender, female athletes demonstrated a stronger correlation between agility and match ranking. Keywords: Squash, Agility, Match Ranking